Stabilizing sulfur vacancy defects by performing "click" chemistry of ultrafine palladium to trigger a high-efficiency hydrogen evolution of MoS2. Issue 18 (1st May 2020) - Liu, Suli; Zhou, Liangliang; Zhang, Wanjia; Jin, Junyu; Mu, Xueqin; Zhang, Sudi; Chen, Changyun; Mu, Shichun
Abstract : A "click" chemistry strategy is used to construct an all-pH efficient hydrogen evolution reaction (HER) catalyst with engineered unsaturated sulfur edges via a strong coupling effect between ultrafine Pd ensembles and Co-MoS2 nanosheets. Abstract : Defect engineering is widely applied in transition metal dichalcogenides to produce high-purity hydrogen. However, the instability of vacancy states on catalysis still remains a considerable challenge. Here, our first-principles calculations showed that, by optimizing the asymmetric S vacancy in the highly asymmetric 1T′ crystal of layered bitransition metal dichalcogenides (Co–MoS2 ) in light of Pd modulation, the relative amount of metastable phase and the quantity of active sites in the structure can be reduced and increased, respectively, leading to a further boosted hydrogen evolution reaction (HER) activity toward layered bi-transition metal dichalcogenides. Thus, we then used a "click" chemistry strategy to make such a catalyst with engineered unsaturated sulfur edges via a strong coupling effect between ultrafine Pd ensembles and Co–MoS2 nanosheets. As expected, the Pd-modulated Co–MoS2 nanosheets exhibited a very low overpotential of 60 mV at 10 mA cm −2 with a small Tafel slope (56 mV dec −1 ) for the HER in 1.0 M PBS, comparable to those of commercial Pt/C. In addition, their high HER activity was retained in acidic and alkaline conditions. Both the theoretical and experimental results revealed that Pd ensembles can efficiently activate and stabilize the inert basal plane S sites during HER processes as a result of the formation of Pd–S in Co–MoS2 . This work not only provides a deeper understanding of the correlation between defect sites and intrinsic HER catalytic properties for transition metal chalcogenide (TMD)-based catalysts, but also offers new insights into better designing earth-abundant HER catalysts displaying high efficiency and durability.